Evolution of High-mass X-ray binaries in the Small Magellanic Cloud. Issue Volume 14:Issue S346(2019) (August 2018) - Yang, Jun; Wik, Daniel R.
Abstract: In order to understand the progenitor of rotation powered pulsars, we compare them with High-mass X-ray binary (HMXB) pulsars, (or X-ray pulsars), in the Small Magellanic Cloud. The plot of period period vs. period derivative shows that isolated neutron stars could be evolved from HMXBs. The pulsars with long spin period might spin up to 0.001-1 s. The mechanism is a third-body interaction that detaches the donor, leaving an isolated, small period neutron star behind.